LEGAL AND ETHICAL ASPECTS OF HOSPITAL RESPONSIBILITY FOR PATIENT SAFETY - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Adisam Publisher, 2025)
Legal and ethical aspects play an important role in a hospital's responsibility for patient safety. Hospitals are required to comply with various laws and regulations that guarantee quality medical service standards, including the Health Act and health accreditation standards. Compliance with these regulations reduces the risk of medical errors and ensures a safe and effective care environment. In addition, ethical aspects require hospitals and medical personnel to apply moral principles such as beneficence, non-maleficence, autonomy, and justice, which promote the welfare, rights, and justice of patients. By combining the fulfilment of legal obligations and ethical principles, hospitals can increase patient trust, prevent malpractice, and ensure the overall safety and well-being of patients.